The role of minimally invasive surgery in epithelial ovarian cancer treatment: a narrative review - Generali, Matteo; Annunziata, Gianluca; Pirillo, Debora; D’Ippolito, Giovanni; Ciarlini, Gino; Aguzzoli, Lorenzo; Mandato, Vincenzo Dario (Frontiers in Medicine, 2023)
Abstract Objectives: The aim of this narrative review is to summarise the available evidence on the use of minimal invasive surgery (MIS) in the management of epithelial ovarian cancer (EOC). Background: MIS is currently performed to stage and treat EOC at different stage of presentation. We will evaluate risks and benefits of minimally invasive surgery for early stage EOC treatment, then potential advantages provided by staging laparoscopy in identifying patients suitable for primary cytoreductive surgery (PDS) will be discussed. Finally we will investigate the growing role of MIS in the treatment of advanced EOC after neoadjuvant chemotherapy (NACT) and in the treatment of EOC recurrence. Methods: An electronic database search was performed on PubMed, Medline, and Google Scholar for relevant studies up to December 2022. Conclusions: LPS represents a feasible surgical procedure for the staging and treatment in early, advanced and EOC relapse in selected patients treated in high-volume oncological centres by surgeons with adequate experience in advanced surgical procedures. Despite the increasing use of MIS over the last few years, randomized clinical trials are still needed to prove its effectiveness Keywords: Minimal invasive surgery; Diagnostic laparoscopy; Early ovarian cancer, Advanced ovarian cancer; Interval debulking surgery; Neoadjuvant chemotherapy; Ovarian cancer recurrence, Cytoreduction.